Polyamorphism and Structural Transformation in Liquid B2O3 under Compression: Insight from Visualization of Molecular Dynamics Data - Mai, Thi Lan (H. : ĐHQGHN, 2017)
The structural order, polyamorphism and structural change of liquid B2O3 at 3000 K and in a 0-40 GPa pressure range are investigated by molecular dynamics simulation. Results show that the network structure of liquid B2O3 is formed from BOx basic structural units (x=3, 4). At ambient pressure, most of basic structural units (coordination units) are BO3 (over 99%). The BO3 basic structural units are linked each to other via OB2 linkages. At high pressure, the network structure of liquid B2O3 comprises of both BO3 and BO4 units linked each to other via OB2 or OB3 linkages. The bond angle and bond length distribution in BOx units is not dependent of pressure. In other word, the topology structure of BOx units in different models is identical. The bond angle distribution in OB2 linkages depends strongly on pressure meanwhile the bond angle distribution in OB3 linkages does not depend on pressure. With increasing pressure, liquid B2O3 transforms gradually from a BO3- network structure (at low pressure) to BO4- network structure (at high pressure). The distribution of BOx in model is not uniform but tends to form the clusters of BOx units. The clusters of BO3 the form low density regions, conversely the clusters of BO4 form the high density regions. The size of low and high density regions is strongly dependent of pressure.